Combustion and Emission Performance of an HCCI Engine Fuelled by n-Heptane/Toluene Blends at a Low-Load Operating Condition - Hongsheng Guo; W. Stuart Neill (Journal of Advanced Thermal Science Research, 2018)
Homogeneous charge compression ignition (HCCI) engine technology offers high fuel efficiency and extra low nitrogen oxide (NOx) and particulate matter (PM) emissions, which makes it a potential alternative combustion mode to conventional diesel engines. A diesel fuel is usually composed of many classes of hydrocarbons among which aromatic compounds have attracted special attention due to their specific combustion characteristics. Understanding the combustion and emission characteristics of different classes of hydrocarbons is crucial for identifying appropriate diesel fuels suitable for HCCI combustion. Toluene is a typical aromatic compound in a diesel fuel. A study of toluene content may provide implications of the effect of aromatic in a diesel fuel on HCCI combustion. In this paper, the combustion and emission performance of an HCCI engine fuelled by n-heptane/toluene blends at a low load operating condition was investigated by experiment and numerical simulation. A modified Cooperative Fuel Research (CFR) engine and a in-house-developed multi-zone model were employed. The engine was operated at the condition of engine speed of 900 rpm, relative air/fuel ratio of 3.5 and without external exhaust gas recirculation. The investigated fuel blends covered a range from pure n-heptane to 70% toluene by volume. Both experimental and numerical results showed that an increase in toluene fraction in the fuel blend retarded combustion phasing. As a result, the optimal compression ratio, at which thermal efficiency reached its maximum for a fuel blend, increased with increasing toluene fraction. The maximum thermal efficiency increased as the toluene fraction increased from 0 to 50%, but then decreased with further increasing toluene fraction to higher values. The peak pressure rise rate also increased with increasing toluene fraction at a constant combustion phasing. An increase in toluene fraction resulted in an increase in unburned hydrocarbon emissions but had little effect on NOx emissions.